Efficiency-Thoroughness Trade-Off Characteristics of Air Traffic Controllers During Tower Operations. (December 2020) - Takagi, Tsubasa; Nakanishi, Miwa
Air traffic demand has been growing for years and many countries are trying to solve this situation by modernizing their national airspace through advanced automation. Those projects aim to provide a greater level of efficiency while ensuring a safe flow of air traffic. However, human air traffic controllers have been coping with difficult situations and unexpected events by flexibly balancing efficiency and thoroughness throughout their operations. In this study, we conducted an experiment using a simulator depicting air traffic control tower operations and analyzed the trade-off decisions made by humans under varying situations. By doing so, we proposed a model with the aim of applying the results to future air traffic management systems. This could allow those autonomous systems to make decisions that are similar to those of human preferences, which could lead to a proactive management of safety and a higher level of automation acceptance.